Contributions of Pathobiological and Translational Science to Understanding and Managing Ischemic Heart Disease: Progress, Impediments, and Future Directions - L. Maximilian Buja, MD (Texas Heart Institute Journal)
Key pathobiological components of ischemic heart disease have been identified as follows: (1) In 1970 to 1973, myocardial infarct size was found to be the primary determinant of prognosis after acute myocardial infarction (AMI); (2) in 1973 to 1989, vulnerable coronary artery plaques were found to predispose individuals to coronary plaque disruption and thrombosis, causing major AMI; (3) in 1972, timely coronary reperfusion was demonstrated to limit the size of evolving AMI but with risk of reperfusion injury; and (4) in 1986, myocardial conditioning was found to be a clinically significant modulator capable of delaying AMI progression. Promising cardioprotective strategies combining timely reperfusion with conditioning in experimental animal and proof-of-concept human studies have not been shown to optimize cardioprotection, and this area of research has stalled. Nevertheless, opportunities for further progress against ischemic heart disease have come from new perspectives and approaches, including (1) recognition that functionally significant ischemic heart disease can result from microvascular dysfunction or epicardial coronary atherosclerosis; (2) rapid diagnosis of AMI subtypes through application of the Universal Definition of Myocardial Infarction based on high-sensitivity cardiac troponin measurements; (3) the Canadian Cardiovascular Society classification of AMI based on stages of tissue injury severity, as detected by advanced imaging; (4) implementation of the occlusion vs nonocclusion MI paradigm to prompt aggressive management of all ST-segment elevation MI and the one-third of non–ST-segment elevation MI with total occlusion; and (5) implementation of the Early Heart Attack Care program, which emphasizes prodromal symptom recognition to prevent AMI progression.